ARK 2022: AWI airborne ultra-wideband radar data covering englacial folds adjacent to the North East Greenland Ice Stream (NEGIS Folds project) - Bons, Paul D; Jansen, Daniela; Paden, John D; Franke, Steven; Steinhage, Daniel; Helm, Veit (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWIs multi-channel ultra-wideband radar system (AWI UWB) during the Arctic season of 2022. The profiles extend the onset part of the Northeast Greenland Ice Stream covering englacial folds adjacent to the ice stream near the EastGRIP ice core drill site. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.
Keywords: AWI UWB; EastGRIP; Greenland ice sheet; NEGIS; Northeast Greenland Ice Stream; radio-echo sounding